Helical chiral N‐heterocyclic carbene ligands in enantioselective gold catalysis - Pallova, Lenka; Abella, Laura; Jean, Marion; Vanthuyne, Nicolas; Barthes, Cécile; Vendier, Laure; Autschbach, Jochen; Crassous, Jeanne; Bastin, Stéphanie; César, Vincent (Chemistry – A European Journal, 2022)
International audience The first chiral helicene-NHC gold(I) complexes efficient in enantioselective catalysis were prepared. The L-shaped chiral ligand is composed of an imidazo[1,5-a]pyridin-3-ylidene (IPy) scaffold laterally-substituted by a configurationally stable [5]-helicenoid unit. The chiral information was introduced in a key post-functionalization step of a NHC-gold(I) complex bearing a symmetrical anionic fluoreno[5]helicene substituent, leading to a racemic mixture of complexes featuring three correlated elements of chirality, namely central, axial and helical chirality. After HPLC enantiomeric resolution, X-ray crystallography and theoretical calculations enabled structural and stereochemical characterization of these configurationally stable NHC-gold(I) complexes. The high potential in asymmetric catalysis is demonstrated in the benchmark cycloisomerization of N-tethered 1,6-enynes with up to 95:5 er.